Development of a hospital virtual tour with virtual reality-based panorama - Permanasari, A.E. (Inderscience Publishers, 2021)
Information technology has an important role in socialising the institutional profile of hospitals as public services. Virtual reality (VR) technology, along with panoramic photography as a multimedia component, supports the need for visualisation that can be made almost as real as the original. In this study, we utilised VR to introduce hospital buildings and their rooms. The multimedia development life cycle method was used in this development. The study aims to analyse the effect of text cueing on panoramic design. Users can explore the hospital tour virtually. User experience questionnaire (UEQ) was used to evaluate each application. The significance level of the comparisons was tested by using the Wilcoxon test. In general, the UEQ assessed both applications in the range above average to excellent scores. The experimental results showed that the approach can enhance user experience aspects such as attractiveness, stimulation, and novelty. Perspicuity, dependability, and novelty were not significantly improved according to the Wilcoxon result. This study implies that using text cueing enhances user experience in a virtual tour with panoramic VR. Copyright Â© 2021 Inderscience Enterprises Ltd.